Effect of the amine group content on catalytic activity and stability of mesoporous silica supported Pd catalysts for additive-free formic acid dehydrogenation at room temperature. (22nd February 2019) - Jin, Min-Ho; Park, Ju-Hyoung; Oh, Duckkyu; Park, Jong-Soo; Lee, Kwan-Young; Lee, Dong-Wook
Abstract: A strong metal-support interaction (SMSI) between amine-functionalized silica supports and Pd nanoparticles is one of important factors to determine the catalytic activity of additive-free formic acid dehydrogenation at room temperature over Pd/NH2 -silica catalysts. However, there are few reports on the effect of the content of amine functional groups on the SMSI and catalytic performance for formic acid dehydrogenation. In this study, we tried to maximize the content of amino-propyl groups on the surface of mesoporous silica supports (KIE-6) via hydroxylation of KIE-6 surface before amine functionalization and investigated the effect of the content of amine functional groups on the catalytic activity and stability for formic acid dehydrogenation. As a result, Pd/NH2 -hydroxylated KIE-6 (Pd/NH2 -OH-KIE-6) catalysts with more amine functional groups provided higher initial catalytic activity (595 mol H2 mol catalyst −1 h −1 ) than Pd/NH2 -KIE-6 catalysts. However, Pd/NH2 -KIE-6 catalysts showed higher catalytic stability in comparison with Pd/NH2 -OH-KIE-6 catalysts. After various characterizations of catalysts, it was demonstrated that the enhanced initial catalytic activity of Pd/NH2 -OH-KIE-6 catalysts is attributed to the higher ratio of Pd/PdO derived from the increased content of amine groups of NH2 -OH-KIE-6 supports. In contrast, the low surface area of NH2 -OH-KIE-6 promoted the aggregation of Pd nanoparticles on Pd/NH2 -OH-KIE-6 catalysts, which resulted in the lower catalytic stability of Pd/NH2 -OH-KIE-6 catalysts than Pd/NH2 -KIE-6 catalysts. Thus it was concluded that confinement of Pd nanoparticles to the pores of supports is a more dominant factor to achieve higher catalytic stability, while the initial catalytic activity is affected by the electronic state of Pd nanoparticle determined by the content of amine functional groups on the surface of supports. Graphical abstract: Image 1 Highlights: A strong metal-support interaction is important determine the catalytic activity. Pd/NH2 -hydroxylated KIE-6 (Pd/NH2 -OH-KIE-6) catalyst was synthesized. Pd/NH2 -OH-KIE-6 provided higher initial catalytic activity than Pd/NH2 -KIE-6. Pd/NH2 -KIE-6 showed higher catalytic stability in comparison with Pd/NH2 -OH-KIE-6.